Art and form : from Roger Fry to global modernism - Rose, Sam (Art historian) (Refiguring modernism, 2019)
"Explores the rise of formalism in the visual arts. Employs an expanded sense of form to rethink a range of areas, including the history of writing about art, constructions of high and low culture, and the idea of global modernism"--Provided by publisher